Effects of Bioreactor‐Oxygenation During Extracorporeal Granulocytes Treatment in Septic Patients. Issue 4 (8th February 2018) - Sauer, Martin; Richter, Georg; Altrichter, Jens; Wild, Thomas; Doß, Fanny; Mencke, Thomas; Ehler, Johannes; Doß, Sandra; Koch, Stephanie; Schubert, Anton; Nöldge‐Schomburg, Gabriele; Mitzner, Steffen R
Abstract: A granulocyte bioreactor for the extracorporeal treatment was developed to enhance the immune cell function in patients with severe sepsis. The influence of oxygenation on the used cells was tested in a prospective clinical study. Ten patients with severe sepsis were treated twice with the granulocyte bioreactor. The used cells were screened for functionality; values of blood gases, glucose and lactate were obtained from the recirculating bioreactor circuit. Five patients were treated with an oxygenator setup (Oxy group), five without oxygenator (Non‐Oxy group). The overall in‐hospital mortality was 50%. Significantly lower values of oxygen saturation, partial oxygen pressure, lactate, oxyburst and phagocytosis were seen in the Non‐Oxy group compared with the Oxy group in the bioreactor circuit. Further studies with this approach are encouraged and should focus on the influence of oxygenation on production of reactive oxygen species and cytokines of used cells.